Solve for c
c=\sqrt{29}-7\approx -1.614835193
c=-\left(\sqrt{29}+7\right)\approx -12.385164807
Share
Copied to clipboard
c^{2}+14c+49-4\left(1+7\right)+3=0
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(c+7\right)^{2}.
c^{2}+14c+49-4\times 8+3=0
Add 1 and 7 to get 8.
c^{2}+14c+49-32+3=0
Multiply 4 and 8 to get 32.
c^{2}+14c+17+3=0
Subtract 32 from 49 to get 17.
c^{2}+14c+20=0
Add 17 and 3 to get 20.
c=\frac{-14±\sqrt{14^{2}-4\times 20}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, 14 for b, and 20 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
c=\frac{-14±\sqrt{196-4\times 20}}{2}
Square 14.
c=\frac{-14±\sqrt{196-80}}{2}
Multiply -4 times 20.
c=\frac{-14±\sqrt{116}}{2}
Add 196 to -80.
c=\frac{-14±2\sqrt{29}}{2}
Take the square root of 116.
c=\frac{2\sqrt{29}-14}{2}
Now solve the equation c=\frac{-14±2\sqrt{29}}{2} when ± is plus. Add -14 to 2\sqrt{29}.
c=\sqrt{29}-7
Divide -14+2\sqrt{29} by 2.
c=\frac{-2\sqrt{29}-14}{2}
Now solve the equation c=\frac{-14±2\sqrt{29}}{2} when ± is minus. Subtract 2\sqrt{29} from -14.
c=-\sqrt{29}-7
Divide -14-2\sqrt{29} by 2.
c=\sqrt{29}-7 c=-\sqrt{29}-7
The equation is now solved.
c^{2}+14c+49-4\left(1+7\right)+3=0
Use binomial theorem \left(a+b\right)^{2}=a^{2}+2ab+b^{2} to expand \left(c+7\right)^{2}.
c^{2}+14c+49-4\times 8+3=0
Add 1 and 7 to get 8.
c^{2}+14c+49-32+3=0
Multiply 4 and 8 to get 32.
c^{2}+14c+17+3=0
Subtract 32 from 49 to get 17.
c^{2}+14c+20=0
Add 17 and 3 to get 20.
c^{2}+14c=-20
Subtract 20 from both sides. Anything subtracted from zero gives its negation.
c^{2}+14c+7^{2}=-20+7^{2}
Divide 14, the coefficient of the x term, by 2 to get 7. Then add the square of 7 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
c^{2}+14c+49=-20+49
Square 7.
c^{2}+14c+49=29
Add -20 to 49.
\left(c+7\right)^{2}=29
Factor c^{2}+14c+49. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(c+7\right)^{2}}=\sqrt{29}
Take the square root of both sides of the equation.
c+7=\sqrt{29} c+7=-\sqrt{29}
Simplify.
c=\sqrt{29}-7 c=-\sqrt{29}-7
Subtract 7 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}